The Application of Software for Understanding English Texts for Students in Peru - Laura De La Cruz, Kevin Mario (2019)
The present article is referred to determine the results of the JClic Software application in comprehension of texts in English, in the students of the secondary level of a school in Peru, in this case at Santa Ana High School, in 2018. It was developed by a pre-experimental design pretest and postest with only one group after the pretest, JClic software was used through computers in laboratories, until taking the exit test at the end of the semester of studies. Of a total of 19 students after CLIC software application, 89.47% of the students have reached an outstanding achievement level, 10.53% of the students are at the expected achievement level, 0% of the students are at process level, and 0% of the students are at the beginning level. From the results obtained it can be affirmed: with the JClic software application, the fourth year students at Santa Ana High School, in 2018; they have managed to improve their level in the comprehension of texts in the affirmative form in English, simple past.